A study on the natural host range of Enterocytozoon hepatopenaei in different species of shrimp and co-habiting aquatic fauna - Shirsak Mondal; Deepika, A.; Hundare, Sagar; Poojary, Nalini; Abraham, T. J; K. Sreedharan; Tripathi, Gayatri; K. V. Rajendran (Indian Journal of Fisheries, 2023)
Enterocytozoon hepatopenaei (EHP) is a serious pathogen impacting farmed shrimpproduction in Asian countries. Though many aquatic organisms were reported to besusceptible to EHP, the full range of susceptible hosts, which have the potential to transmitthe pathogen to shrimp has not been identified. In this study, a range of farmed and wildinvertebrates and other cohabiting fauna from different ecological niches located in thecoastal and inland saline areas were subjected to PCR-based detection employing primerstargeting three different genes coding for small subunit (ssu) rRNA, spore wall protein(SWP) and β-tubulin. The PCR analysis with ssu-rRNA primers showed positive amplificationin Penaeus vannamei, Penaeus monodon, Penaeus indicus, marine shrimps, aquatic insect,mud crabs, freshwater crab and violet clam. PCR using SWP primers detected EHP inP. vannamei, P. monodon, aquatic insect and marine crabs, while the β-tubulin primersresulted in positive amplification only in mud crabs and P. vannamei. The PCR ampliconsrevealed 99-100% identity with the sequences of EHP. The present study forms the firstattempt to screen a wide range of aquatic fauna for EHP employing three different PCR testsand the findings are significant as these organisms have the potential to be carriers of EHPand are likely to transmit the parasite to shrimp culture systems.Keywords:Co-habiting aquafauna, Enterocytozoonhepatopenaei, EHP, Host range, Shrimp culture